2014
DOI: 10.1186/1756-3305-7-128
|View full text |Cite
|
Sign up to set email alerts
|

Birds as potential reservoirs of tick-borne pathogens: first evidence of bacteraemia with Rickettsia helvetica

Abstract: BackgroundBirds have long been known as carriers of ticks, but data from the literature are lacking on their role as a reservoir in the epidemiology of certain tick-borne disease-causing agents. Therefore, the aim of this study was to evaluate the presence of three emerging, zoonotic tick-borne pathogens in blood samples and ticks of birds and to assess the impact of feeding location preference and migration distance of bird species on their tick infestation.MethodsBlood samples and ticks of birds were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
2
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(136 citation statements)
references
References 26 publications
6
119
2
9
Order By: Relevance
“…Molecular analysis was also performed with PCR and sequencing, in order to compare the tick with other tick isolates of which relevant data are available in the GenBank. The DNA was extracted from one hind leg of the tick as described (Hornok et al, 2014b).…”
mentioning
confidence: 99%
“…Molecular analysis was also performed with PCR and sequencing, in order to compare the tick with other tick isolates of which relevant data are available in the GenBank. The DNA was extracted from one hind leg of the tick as described (Hornok et al, 2014b).…”
mentioning
confidence: 99%
“…However, the competence of birds to function as Rickettsia reservoir capable of transmitting and infecting ticks with rickettsiae is not yet completely understood [29]. A recent study has detected bacteraemia by R. helvetica in wild avian hosts in Hungary [4], but further data about Rickettsia spp. infections in birds are not available worldwide.…”
Section: Discussionmentioning
confidence: 98%
“…A recent molecular study has been carried out on ticks collected from migratory birds in Italy, which found that they are often carriers of ticks, in particular Hyalomma marginatum, infected by Rickettsia sp, B. burgdorferi s.l., C. burnetii and Babesia microti [5]. However, data about the detection of tick-borne bacteria in birds are scant [4,6,7,8], and in particular, there is no data available on the prevalence of these pathogens among birds in Italy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, wild birds are among the most mobile hosts, and therefore they may be regarded as hosts with relevant potential in the dispersion of ticks and tick-borne diseases, including rickettsial organisms (ELFVING et al, 2010;HORNOK et al, 2014;BERTHOVÁ et al, 2016). Among 127 species of Ixodidae established in the Neotropical Zoogeographic Region (GUGLIELMONE et al, 2014;NAVA et al, 2014a, b;KRAWCZAK et al, 2015), 39 are found in Argentina (GUGLIELMONE & NAVA, 2005, 2006NAVA et al, 2009NAVA et al, , 2014a.…”
mentioning
confidence: 99%